Serotyping of dengue virus in 2016-17 outbreak in Kudat, Sabah, Malaysia - Aung, Than Tin; Timothy Jr Gintarong; Nor Amalina, Emran; Tin, Tin Thein; Chua, Tock Hing (Malaysian Society of Parasitology and Tropical Medicine, 2020)
An outbreak of dengue in Kudat, northern Sabah in 2016-2017 provided an opportunity to investigate the circulating serotypes of dengue viruses of cases at Hospital Kudat. Between September 2016 and December 2017, a total of 156 dengue positive sera(tested positive by either NS1 antigen, or IgM & IgG antibody rapid test) were collected from dengue patients who had acute fever and showed signs and symptoms suggestive of dengue. RNA was extracted from the sera using QIAamp RNA Blood Mini Kit, and molecular amplification was performed using one-step RT-PCR kit, followed by nested PCR using HotStart Taq master mix kit with the primers of the dengue C-prM gene. There were 81 (52%) male and 75 (48%) female cases. The age group with the highest number of cases was the 10-19 years old, while the youngest infected was 8 months old and the oldest was 83 years old. RT-PCR results showed 88 sera dengue positive, 48 infected with a single serotype while another 40 with multiple serotypes. All four DENV serotypes were co-circulating during the outbreak period and DENV-1 was predominant. Molecular analysis also indicated 69.2%, 50.0%, 51.9% and 48.9% respectively of the NS1, IgM, IgG and IgM & IgG positive sera were RT-PCR positive for dengue. High number of cases were seen in December 2016, February and May 2017. The dengue outbreak might be related to switching of predominant serotype from DENV 4 to DENV 1.